2003
DOI: 10.1016/s0266-7681(02)00394-7
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Year Outcome Following Colles’ Type Distal Radial Fracture. A Comparison of Two Treatment Methods

Abstract: Eighty-five patients were reviewed 7 years after prospective randomization to bridging external fixation or plaster immobilization for treatment of a Colles' type distal radial fracture. The Gartland and Werley score showed that most patients in each group had an excellent or good outcome and patient satisfaction was comparable and high in both groups. The fixator group had significantly less radial shortening (P<0.05). Despite a high level of radiographic malunion (50%) overall function, range of movement and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 21 publications
0
32
1
1
Order By: Relevance
“…However, Cassebaum concluded that good function ensued, despite poor anatomical results [2]. Some authors have shown that there is no correlation between functional outcome and satisfactory radiological results [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, Cassebaum concluded that good function ensued, despite poor anatomical results [2]. Some authors have shown that there is no correlation between functional outcome and satisfactory radiological results [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies that have evaluated outcomes of distal radius fractures from the perspectives of patient satisfaction, perception of disability, and quality of life after the injury did not find associations with radiographic outcome, suggesting that a well-treated bone lesion does not guarantee patient satisfaction [1,7,13,16,33]. This finding may be explained by the presence of associated soft-tissue lesions that were not recognized or treated.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were randomised to bridging external fixation or plaster immobilisation. The conservatively managed group demonstrated worse radiographic findings, with wrist arthritis and radial shortening but no difference in upper limb function was demonstrated (Young et al, 2003). These studies highlight the lack of consensus as to what degree of radiographic malunion is considered to be acceptable.…”
Section: Radiographic Malunion Predicting Functional Outcomesmentioning
confidence: 84%